Um modelo para controle biológico de pragas associado ao uso de pesticidas - Frank, Adriane (2014)
In this work we propose a Coupled Map Lattice to study a predador-prey system where the prey is a pest and the predador is a biological control agent. We consider that the strategy of biological pest control is combined with a planned use of pesticides. That is, the chemical is sprayed only when the prey density is higher than the threshold control. Furthermore, application of chemical is made only in the patches of high pest infestation. In the absence of the chemical prey and predators move by diffusion. However, when the chemical is sprayed, the individuals have an escape behavior and they move from patches with high concentrations of the chemical to others with lower concentrations. The chemical, in turn, spreads by diffusion and by wind. The simulation results show that the initial distribution of predators can have great effect on the system dynamics and therefore the efficacy of biocontrol.